FEATURES EVALUATION OF INNOVATIVE DEVELOPMENT COMPANY - E. V. Martynova (Финансы: теория и практика, 2017)
The article describes an innovative approach to the assessment of the company. Copyright formulated a definition of «innovative development company,» highlighted the indivisible triumvirate of macroeconomic, microeconomic and meso-economic factors affecting the level of innovation of business entities. The necessity and feasibility assessment of the level of innovation of the company through the prism of its innovation potential. The model of determining the integral criterion of innovative development company. Highlights the key components of assessing the level of innovation of the company.